Impact of women’s political empowerment through gender quotas on improved drinking water access in Africa - Jiafu An; Tenghui Wang; Bin Chen; Peng Gong; Chen Lin; Nils Chr. Stenseth (Proceedings of the National Academy of Sciences, 2025)
Access to safely managed drinking water is a fundamental human right, essential for human health and well-being. However, 2.2 billion people around the world still lack this access, with significant geographical disparities. In this study, we leveraged the implementation of gender quota laws—specifically reserved parliamentary seats for women across African countries—to examine its impact on improved water availability. Our findings reveal that the implementation of gender quotas is associated with a 4.71 percentage point increase, on average, in the likelihood of people accessing safely managed water infrastructure. This effect becomes even more pronounced, rising to a 12.25 percentage point increase, when the quotas mandate reserving more than 20% of seats for women. Households with lower wealth, female-headed households, those living in rural areas, and households with lower levels of women’s empowerment and education benefit most from this policy. Further investigation into the underlying mechanisms, and anecdotal evidence, reveals that gender-reserved seat quotas lead to an increase in the proportion of women in parliaments and an expansion of women’s political and social rights, although these effects do not extend to economic status.